2014
DOI: 10.1007/s11205-014-0788-2
|View full text |Cite
|
Sign up to set email alerts
|

Do Active Labour Market Policies Promote the Well-Being, Health and Social Capital of the Unemployed? Evidence from the UK

Abstract: In recent decades, one of the most notable developments in social policy has been the expansion of active labour market policies (ALMPs): training schemes that aim to speed up unemployed people's return to the labour market. At the same time, academic and political attention has begun to rethink the traditional ways in which social policies like ALMPs should be evaluated: away from typically economic-oriented outcomes towards health and social indicators, such as subjective well-being and social capital. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 49 publications
4
60
0
2
Order By: Relevance
“…Studies from Australia, Germany and the UK have found positive effects of activation interventions on participant well‐being, whilst other research from Denmark and Sweden provides mixed results, and in some cases finds no association between participation and subjective well‐being (Sage ), leaving us with a mixed and ambiguous international picture. Of particular relevance to the present article, Sage (, ) finds that participants in UK activation schemes do, on average, report higher levels of well‐being than the openly unemployed, controlling for a range of other factors, leading him to the conclusion that these activation schemes can offer a form of intermediate labour market status between open unemployment and paid work. Importantly, however, although hampered by small sample size, Sage's () findings further suggest variation in process well‐being effects across different types of activation programme.…”
Section: Activation Typologies and Process Well‐being: A Neglected Evmentioning
confidence: 78%
See 1 more Smart Citation
“…Studies from Australia, Germany and the UK have found positive effects of activation interventions on participant well‐being, whilst other research from Denmark and Sweden provides mixed results, and in some cases finds no association between participation and subjective well‐being (Sage ), leaving us with a mixed and ambiguous international picture. Of particular relevance to the present article, Sage (, ) finds that participants in UK activation schemes do, on average, report higher levels of well‐being than the openly unemployed, controlling for a range of other factors, leading him to the conclusion that these activation schemes can offer a form of intermediate labour market status between open unemployment and paid work. Importantly, however, although hampered by small sample size, Sage's () findings further suggest variation in process well‐being effects across different types of activation programme.…”
Section: Activation Typologies and Process Well‐being: A Neglected Evmentioning
confidence: 78%
“…Whilst there is much general empirical support for these theories (Creed and Klisch ; Paul and Batinic ; Wulfgramm ; Selenko et al . ), there has however been remarkably little empirical attention specifically on the question of how variation in the type of activation policies links to variation in well‐being effects amongst unemployed people (see Sage for a review). Strandh's () investigation into ALMPs in the Swedish context offers a notable exception in its comparison of the process well‐being effects of three different types of activation measures:
Workplace participation : full‐time, self‐directed work experience in the regular labour market with participants themselves finding an employer to take them on. High‐quality training and education : high‐quality theoretical and vocational training courses delivered by specialist or mainstream education providers and leading to formal qualifications. Informal employment‐preparation tasks : light touch employability‐type activities involving only unemployed people, taking place outside of the normal labour market, intended simply to keep unemployed participants busy and engaged and viewed as a last resort where no other preferable alternatives could be found.
…”
Section: A Framework For Understanding Variation In Active Labour Marmentioning
confidence: 99%
“…The second measure of health is based on the 12 item General Health Question (GHQ12) which measures mental health [40]. This is consistently measured across the BHPS and USS data, and the Likert version, that is the total value of the scores of its items, is adopted in this study [41][42][43].…”
Section: Methodsmentioning
confidence: 99%
“…Although there is extensive literature on the differential effects of unemployment between genders, less is in known about the gender differential effects of ALMPs on health. One of the few published studies, a cross-sectional study from the UK, showed that life worth and happiness was higher among employed than unemployed male ALMP participants, and among females, participation had a marked effect on life satisfaction (5). Rojdalen et al (38) also designed a non-experimental study based on retrospective judgments in Sweden, taking gender differences into account.…”
Section: Gender Differences Of Almps On Healthmentioning
confidence: 99%